Pengembangan Media Pembelajaran Interaktif Untuk Siswa Autisme SLB Negeri 2 Mataram - Ida Susanti; Siti Komariah (Educational Note, 2025)
This study aims to develop interactive learning media tailored to the characteristics and needs of students with autism at SLB Negeri 2 Mataram. Students with autism require specific, structured, and engaging instructional approaches to ensure that the learning process can take place effectively. The research method employed was Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). During the analysis phase, a needs assessment was conducted through observations and interviews with teachers and parents. The media design was developed based on the findings of this analysis, focusing on attractive visualizations, simple navigation, and quick responses to user interaction. The media was developed in the form of an Android-based interactive application containing basic learning materials such as reading, counting, and recognizing surrounding objects. A limited trial was conducted with five students with autism, supported by accompanying teachers. The evaluation results indicated that the media significantly helped improve students’ attention and participation during the learning process. Both teachers and students responded very positively to the media, particularly due to its audio features, animations, and immediate feedback, which align with the visual and kinesthetic learning styles commonly associated with students with autism. In conclusion, this interactive learning media is feasible to use as an innovative alternative to support inclusive and enjoyable learning processes for students with autism at SLB Negeri 2 Mataram.